Staging Expertise in Times of COVID-19: An Analysis of the Science-Policy-Society Interface in the Dutch “Intelligent Lockdown” - Prettner, Robert; te Molder, Hedwig; Hajer, Maarten A.; Vliegenthart, Rens (Frontiers in Communication, 2021)
The corona crisis of 2020 took many by surprise. Quite suddenly, politicians had to make drastic decisions to guarantee public health, affecting basic civil liberties. In justifying their decisions, politicians internationally reverted back to a direct ‘staging’ of experts to legitimize their proposals for what internationally became known as the ‘lockdown’. In this article we analyse the performance of the Dutch government that, early on, labelled its approach to COVID-19 as an ‘intelligent lockdown’. Our analysis examines the dramaturgy of expertise of the Dutch ‘intelligent lockdown’. We selected two interrelated ‘stages’: the official press conferences, fully controlled by the government, and the responses on Twitter, as focal channel for critique from the general public, but also from opposition parties and (alleged) experts. 26 press conferences of the Dutch Prime Minister were analysed and a search for the most popular posts on Twitter referring to the press conference(s) was carried out covering the period between 6th of March and 29th of May 2020. The results show that the technocratic framing of expertise remained stable during the sampling period, regarding (1) the undisputed status of expertise as the clear-cut basis for decision-making in uncertain times, and (2) the dominance of the same epidemiological and virological experts throughout this period. Framing on Twitter challenged the omnipotence of the experts advising the government in various ways, namely, by referring to dissenting opinions of other experts, by questioning the underlying motives of experts’ advice or by pointing out that the policies were clearly contrary to everyday experience. We argue that it is not so much the facts themselves that are at stake here but hidden moralities, which include the government’s alleged complacency while asking citizens to blindly trust, its unpredictable behaviour in the light of the promised straight line between scientific evidence and policy making, and its motivated behaviour while claiming that the facts speak for themselves.